Analisis perilaku Sticky Cost biaya produksi pada perusahaan BUMN sektor manufaktur periode 2014-2020 - Dinda Puri Safitri; Ika Kristianti (Politeknik Ganesha Medan, 2022)
The purpose of this study is to find out if there are indications of sticky cost behavior that exists in production costs. Sticky cost can be indicated by the response of production costs to changes in net sales. This research is empirical research using multiple linear regression analysis. This research sample is a state-owned company, especially the manufacturing sector, which existed in the current period from 2014 to 2020. Samples are taken by purposive sampling method. The total number of samples of state-owned enterprises in the manufacturing sector used is as many as 49 samples. This research is expected to provide benefits that are used as a reference in the development of literature with regard to cost behavior or sticky costs. In addition, another hope of this sticky cost-related research can help provide benefits that can later be used as input to managers in planning costs, because not all costs can change proportionally. From the manager's side, of course, this research is an evaluation material that will later be used for reference in decision making so that there is no indication of sticky cost behavior. The conclusion of this study is that the production cost means that it shows that registered SOE manufacturing has sticky behavior where there is no decrease in production costs when net sales decrease, so that variable production costs are not affected. This is because the components in production costs are mostly fixed costs whose increases and also decreased costs are strongly influenced by changes in activity volume, and few variable cost components on production costs.